Profile of Hard skills and Soft skills of Mathematics Education Students - Tri Nopriana; Siska Firmasari; Bambang Avip Priatna Martadiputra (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
This study analyzes some hard skills (problem-solving abilities, level of logical thinking, and geometric thinking) and soft skills (students' self-concept and mathematical habits of mind) mathematics education students explicitly in the first year. The research method used is descriptive quantitative. From the population of all mathematics education students in the first year, one group of students was selected as a random sample using analysis techniques, data presentation, and conclusion drawing. Based on the research results, mathematics education students' overall ability in the first year is already good. Students were mastering five reasoning on the test of logical thinking (TOLT). It means they have solved problems with reasoning associated with proportional or ratio, control variables, probability,Â correlation and combinatorics.Â Most students have reached the level of thinking geometry at the analysis stage; that is, students have already understood the properties of concepts or geometry based on informal analysis of parts and component attributes. However, students do not have good soft skills. Even though they have a strong habit of mind, students' self-concept is quite sufficientÂ